Inclination towards entrepreneurship among university students: An empirical study of Malaysian university students - Ooi, Yeng Keat; Selvarajah, Christopher; Meyer, Denny (Center for Promoting Ideas (CPI), USA, 2011)
This study investigates the inclination towards entrepreneurship among university students in the northern region of the Peninsular Malaysia. Specifically, it aims to examine the relationship between entrepreneurship education and inclination towards entrepreneurship. The influence of demographic characteristics and family business background on university students’ inclination towards entrepreneurship is also being examined.An empirical test carried out on the data gathered from questionnaires demonstrates that two entrepreneurship education variables are found to have statistically significant relationship on the inclination towards entrepreneurship. At the meantime, two demographic variables and a family business background variable have an effect on university students’ inclination towards entrepreneurship.Finally, based on the findings, the implications of the study have been forwarded.